Peningkatan kapasitas digital marketing UMKM binaan Suku Dinas PPAPP Jakarta Pusat melalui pelatihan fotografi dan katalog produk elektronik - Annisa, Intan Tri; Deviastri, Lily; Fadhilah, Penny Rahmah (Penamas: Journal of Community Service, 2026)
This community service activity aims to provide photography training and the creation of electronic product catalogs to MSMEs assisted by the Suku Dinas Pemberdayaan, Perlindungan Anak dan Pengendalian Penduduk (DPAPP) Central Jakarta. The program was held at YARSI University and attended by 28 MSMEs from various sub-districts in Central Jakarta. The methods employed included lectures, interactive discussions, and training sessions. This training covered basic photography theory, including lighting techniques for using a mobile phone camera to produce attractive photos. In the practical session, participants practiced taking pictures from various angles and positions to understand the importance of technique in product photography. The activity results showed an increase in knowledge of the material and the training provided. This activity demonstrated that the training was highly effective, helping MSMEs produce more attractive electronic product photos and posters.